"Help Them Understand the Complexity, the Difficulties and the Pleasures of Creative Writing": Children's Author Libby Gleeson on Creativity in Education. Issue 2 (3rd July 2017) - Xerri, Daniel
ABSTRACT: Nurturing young people's creativity seems to have become one of the foremost goals of education over the past few years. However, a minimal amount of attention is paid to the challenges that teachers face in achieving this goal in the classroom. In this interview-based article, children's author Libby Gleeson indicates that while an assessment-driven curriculum undermines teachers' efforts to promote creativity, equally detrimental is their own inability to position themselves as creative practitioners. Based on her professional experience as a writer and educator, Gleeson suggests that teacher education and development can play a pivotal role in helping teachers to nurture their personal creativity.